ASSESSMENT OF THE EFFICACY OF SELECTIVE NONSTEROIDAL ANTI-INFLAMMATORY DRUGS IN RHEUMATOID ARTHRITIS - Solikhov B.M. (World Scientific Research Journal, 2025)
Annotation: Objective: To evaluate the effectiveness of therapy with celecoxib in patients with rheumatoid arthritis. Material and methods: The patients under observation were divided into two groups. 25 patients in the first group were prescribed 10 mg of methotrexate as basic anti-inflammatory therapy per week, while 25 patients in the second group were prescribed celecoxib at a dose of 200 mg twice a day in combination with 10 mg of methotrexate per week for basic anti-inflammatory therapy. Results: In the second group of patients treated with celecoxib, a significant decrease in the number of inflamed and painful joints, ESR, C-reactive protein, VAS, DAS-28 scales, and HAQ index was observed compared to the first group. Conclusion: It has been established that combined therapy with the drug celecoxib can reduce disease activity more effectively in RA patients compared to monotherapy with methotrexate.